2007
DOI: 10.1166/jnn.2007.071
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metal Powder Packing on the Conductivity of Nanometal Ink

Abstract: The power of nanotechnology is realized in its application in numerous areas. One such area is undoubtedly the use of metallic nanoparticles as a direct write application. An effort in this area has resulted in a conductive ink whose conductivity approaches 60-70% that of the bulk copper. Such an ink has been developed by reducing silver, gold, and copper nano-sized powders by a wet method and followed by a heat treatment at less than 400 degrees C. The conductivity of the resulting ink product was found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…There are several methods for preparing nano to micron sized copper powder, including a mild hydrothermal process (Liu et al 2007), a pulsed power technique (Sarathi et al 2006), mechanical milling (Wu et al 1998;Srikanth et al 2004) and wet chemical methods (Hsu et al 1990;Kim et al 2007). Previous authors were able to obtain up to 20 g solid particles (Hsu et al 1990) and should be considered as low yield.…”
Section: Introductionmentioning
confidence: 99%
“…There are several methods for preparing nano to micron sized copper powder, including a mild hydrothermal process (Liu et al 2007), a pulsed power technique (Sarathi et al 2006), mechanical milling (Wu et al 1998;Srikanth et al 2004) and wet chemical methods (Hsu et al 1990;Kim et al 2007). Previous authors were able to obtain up to 20 g solid particles (Hsu et al 1990) and should be considered as low yield.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there have been numerous studies regarding the manufacturing of nanosized metal particles on nanoink applications [1][2][3][4]. Metal inks containing nanoparticles can be used in the fabrication of a variety of printed electronics [5][6][7], such as flexible antennas [5], displays [8], and printed circuit boards [9].…”
Section: Introductionmentioning
confidence: 99%
“…In the wet method, the size of the reduced particles is mainly influenced by factors like the concentration of metal ions, pH, temperature, and reducing agent [1]. In previous studies, the research team demonstrated that the aqueous electrical conductivity can be altered by the reducing agent and the concentration of metal ions in the solution, which can also influence the size of the nanoparticles [3]. One way to increase the copper particle size in solution by this means is to increase the copper ion concentration, causing reduced metal seeds to collide with one another and grow into larger metal nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The market for printable electronics such as displays [1][2][3] and circuit board [1][2][3][4][5] has greatly increased in 21 st century. The conductivity of nano paste and inks using nano sized particles in media has been a crucial factor for electronics patterns for the advanced [1] and flexible electronic devices [3].…”
Section: Introductionmentioning
confidence: 99%
“…The conductivity of nano paste and inks using nano sized particles in media has been a crucial factor for electronics patterns for the advanced [1] and flexible electronic devices [3]. Electronic devices patterned with nano inks have conductivity in the range of ~30% [1][2][3] that of bulk state metal.…”
Section: Introductionmentioning
confidence: 99%